2016
DOI: 10.4196/kjpp.2016.20.5.499
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal acclimation in sudomotor function evaluated by QSART in healthy humans

Abstract: The quantitative sudomotor axon reflex testing (QSART) is a classic test of routine postganglionic sudomotor function. We investigated sudomotor function by QSART after summer (July 2012) and winter (January 2013) seasonal acclimation (SA) in the Republic of Korea. QSART with acetylcholine (ACh) iontophoresis were performed to determine directly activated (DIR) and axon reflex-mediated (AXR1, 2) sweating rate. Onset time of axon reflex, activated sweat gland density (ASGD), activated sweat gland output (ASGO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Based on previously reported data (42), a power calculation (G ϫ Power 3.1.9.2) suggested that a minimum of six participants were required to demonstrate a significant difference in the absolute esophageal temperature achieved following 60 min of uncompensable heat stress before (38.6 Ϯ 0.1°C) and following heat acclimation (38.4 Ϯ 0.1°C) in physically active individuals, with ␤and ␣-values equal to 0.95 and 0.05, respectively. All participants commenced the study during the winter months to mitigate any potential influence of partial acclimation associated with seasonal variation (50,55). A total of eight people (six men, two women, age: 27.6 Ϯ 6.0 yr) completed the study.…”
Section: Participantsmentioning
confidence: 99%
“…Based on previously reported data (42), a power calculation (G ϫ Power 3.1.9.2) suggested that a minimum of six participants were required to demonstrate a significant difference in the absolute esophageal temperature achieved following 60 min of uncompensable heat stress before (38.6 Ϯ 0.1°C) and following heat acclimation (38.4 Ϯ 0.1°C) in physically active individuals, with ␤and ␣-values equal to 0.95 and 0.05, respectively. All participants commenced the study during the winter months to mitigate any potential influence of partial acclimation associated with seasonal variation (50,55). A total of eight people (six men, two women, age: 27.6 Ϯ 6.0 yr) completed the study.…”
Section: Participantsmentioning
confidence: 99%
“…The sweating responses of individuals living in Japan are more pronounced in summer than in winter 18 . The changes in sweating activity measured by the QSART con rmed the involvement of the peripheral nervous system in altering sudomotor activity during seasonal acclimation 19 .…”
Section: Discussionmentioning
confidence: 70%
“…31 The changes in sweating activity measured by the QSART confirmed the involvement of the peripheral nervous system in altering sudomotor activity during seasonal acclimation. 32 In this study, we assessed both sweating ability and its association with the clinical severity of Raynaud's symptoms in patients with SCTDs. We found that none of the disease groups showed an apparent decrease in sweat volume compared to healthy participants (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…QSART was performed in the similar method as used in previous studies (17,(30)(31)(32). For quantification of sweat secretion by QSART, 10% ACh chloride solution was used as a neurotransmitter.…”
Section: Quantitative Sudomotor Axon Reflex Testmentioning
confidence: 99%